PERHITUNGAN ULANG PERENCANAAN STRUKTUR GEDUNG MENGACU KEPADA PERSYARATAN FEMA DAN ASCE/SEI 7-10 - , Andre Ricky, Ashar Saputra, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Earthquake is a natural phenomenon which was happening frequently in Indonesia. Earthquake can make ground motion which affect to the existing building structure. Therefore, in designing building structure, every designer must consider the existence of that earthquake. This research used FEMA 450 and ASCE 7-10 in evaluating building structure due to earthquake with case study IGD Building, Clinic Building, and Administration Building of Academic Hospital of UGM. This research was done by numerical method by using SAP2000 version 11 software. Data which was needed as input of software was got from as built drawing Academic Hospital UGM and Structure Calculation Report from PIU-UGM to model IGD Building, Clinic Building, and Administration Building of Academic Hospital of UGM. Earthquake modeling was done by using response spectrum from the software that contained the newest earthquake data with value of R is equal to 3.5 and 4. That modeling produced output which was used as comparing data to the building safety acceptance criterion, that were drift and member forces. But, before evaluating member forces of structure elements, the existence of P-delta and torsional irregularity effect had to be evaluated because it could affect to the load combination which was used to know the member forces. The result of recalculation showed that modeling of IGD Building, Clinic Building, and Administration Building of Academic Hospital of UGM fulfilled the requirements for drift limits. The value of q for those three buildings was less than the limit so the P-delta effect could be ignored. Torsional irregularity effect analysis was included in the analysis. From the running result of the software, member forces from some elements of those three buildings were found and some elements could not hold shear forces and there were capacity ratios which were bigger than the limit for some elements according to acceptance criteria.